DEVELOPMENT OF HALAL TOURISM DESTINATIONS BASED ON LOCAL WISDOM IN BIREUEN REGENCY IN IMPROVING COMMUNITY ECONOMY - Fuadi; Epi Safira; Nazli Hasan; Falahuddin; Rico Nur Ilham (CV. RADJA PUBLIKA, 2025)
This study aims to determine how the development of local wisdom-based halal tourist destinations in Bireuen Regency in improving the community's economy. The research method in this study uses qualitative methods. The informants in this study were the Bireuen Regency Tourism Office, tourism managers, business owners and visitors. The data collection techniques used are observation and interviews and documentation. The core research results show that the development of local wisdom-based tourist destinations in improving the community's economy is optimal. uphold Islamic values in every tourist destination in Bireuen Regency. Worship facilities and infrastructure are available in every tourist destination. In addition, the community around the tour to get an increase in visitors carries out a promotion strategy by using social media to promote. In line with that, the Bireuen Regency Government through the Tourism Office collaborates to create synergy together in improving the economy of the local community through tourism development.